ATIM-47. NIVOLUMAB VS BEVACIZUMAB IN PATIENTS WITH RECURRENT GLIOBLASTOMA: EXPLORATORY ANALYSIS OF MGMT METHYLATION STATUS AND BASELINE CORTICOSTEROID USE. (11th November 2019) - Weller, Michael; Reardon, David; Brandes, Alba; Sampson, John; Mulholland, Paul; Wick, Antje; Baehring, Joachim; Ahluwalia, Manmeet; Roth, Patrick; Bähr, Oliver; Phuphanich, Surasak; Sepulveda, Juan; et al.
Abstract: BACKGROUND: Current therapies for recurrent glioblastoma provide limited survival benefit. In the open-label, phase 3 CheckMate 143 study (NCT02017717), although the primary endpoint was not met, the median overall survival (mOS) was comparable between nivolumab (anti–PD-1) and bevacizumab in the overall population of patients with glioblastoma at first recurrence after temozolomide chemoradiotherapy (Reardon et al, WFNOS 2017). Exploratory subgroup analyses were conducted to evaluate the association of O-6-methylguanine DNA methyltransferase ( MGMT ) promoter methylation status and corticosteroid use at baseline with mOS. METHODS: Prespecified patient subgroups included MGMT promoter status (methylated vs unmethylated) and baseline corticosteroid use (yes [within 5 days of first dose] vs no). FINDINGS: Methylation status was available for 102/184 (55%) nivolumab-treated and 109/185 (59%) bevacizumab-treated patients. Using a multivariable Cox proportional hazards model analysis, no baseline corticosteroid use (HR, 0.59 [95% CI, 0.36–0.95]) and methylated MGMT status (HR, 0.47 [95% CI, 0.29–0.78]) were each associated with longer mOS among nivolumab-treated patients. Among patients with methylated MGMT and no baseline corticosteroid use, mOS was 17.0 months with nivolumab (n=31) and 10.1 months with bevacizumab (n=22; HR, 0.58 [95% CI, 0.30–1.11]). In patients with methylated tumors and baseline corticosteroids, mOS was 7.7 months with nivolumab (n=12) and 13.5 months with bevacizumab (n=17). Among patients with unmethylated tumors and no baseline corticosteroids, mOS was 8.3 months with nivolumab (n=30) and 10.3 months with bevacizumab (n=29). In patients with unmethylated tumors and baseline corticosteroids, mOS was 5.6 months with nivolumab (n=28) and 8.3 months with bevacizumab (n=28). CONCLUSION: A trend toward longer mOS with nivolumab was observed in a subgroup of patients with methylated MGMT and no baseline corticosteroid use. These findings suggest that MGMT methylation status and corticosteroid use at baseline could be used to identify patients who may benefit from nivolumab and thus warrant further study.